Global Heritage Stone: Estremoz Marbles from Portugal - Lopes, Luís (2015)
The Estremoz Anticline is a Variscan structure that has a Precambrian core and younger rocks aged Devonian Period. The marbles exploited as dimension stone occupy an intermediate stratigraphic position in the Cambrian age Volcano Sedimentary Sequence. The Variscan Orogeny was performed twice with different intensities under ductile and brittle tension fields. The Alpine Cycle also acts and causes more fracturing of the marbles. The geological features imprinted in the marbles are beautiful aesthetic patterns highlighted when used as Dimension Stone. A long term continuous exploitation have been carried out since the Roman period. Pieces of art made with Estremoz Marbles were exported abroad and can be found in Museums and Archaeological Sites throughout Europe and North Africa countries. Present day Estremoz Marble’s production can be found all over the World. The marble based built heritage is omnipresent in the cities region. The historical and widespread application of these marbles in National and International Monuments, some of them already part of the UNESCO World Heritage Sites, is a condition to propose them as Global Heritage Stone Resource for their international recognition. References Lopes, L. & Martins, R. 2014. Global Heritage Stone: Estremoz Marbles, Portugal. From: Pereira, D., Marker, B. R., Kramar, S., Cooper, B. J. & Schouenborg, B. E. (eds) Global Heritage Stone: Towards International Recognition of Building and Ornamental Stones. Geological Society, London, Special Publications, 407, http://dx.doi.org/10.1144/SP407.10